Crisis, poverty and hunger. Food sovereignty as an alternative - HIDALGO MORATAL, Moisés (Revista Iberoamericana de Estudios de Desarrollo)
In this paper we analyse the causes behind the recent food crises (2008, 2011) through the study of the evolution of neo-liberal globalisation and the current world crisis. We seek the causes of hunger in factors such as the growing inequalities in income and the evolution of prices in world agricultural markets. We also analyse certain methods for measuring under-nourishment, with the aim of selecting those that we consider most coherent in order to to achieve this end, by making a number of critical observations on the subject. In accordance with various widely proven theories, we hold that food crises occur as a consequence of structural lack of the right to access to food, and not as a result of a non existent food shortage. In this context, we examine the alternative possibilities currently offered by food sovereignty, a concept that originates in international social movements and which has been found in the daily life of various rural areas, and is, at the same time, consistent with several critical theories originating from the academic world